Understanding Rural Women in Migrant Households: Socio-Economic, Psychological, and Communication Dimensions - Dr. Sunitha N H,; Dr. Manjunatha Bhanuvally,; Dr. Vanishree S,; Dr. Bhavani Kammar, (Public Health, 2026)
The migration of household members profoundly impacts the lives of rural women, shaping their socio-economic status, communication patterns, and psychological well-being. This review explores the multifaceted characteristics of rural women from migrant households, highlighting the socio-economic challenges they face, including increased financial responsibilities, altered family dynamics, and limited access to resources. The study also delves into the psychological effects, such as anxiety, loneliness, and emotional resilience, arising from prolonged separations and evolving roles. Furthermore, the review examines how migration influences communication practices, emphasizing the adoption of modern communication tools and the role of social networks in maintaining familial bonds and fostering community engagement. By synthesizing insights from various studies, this article provides a comprehensive understanding of the interplay between migration and the socio-economic, psychological, and communication dimensions of rural women's lives. These findings underscore the need for targeted interventions and policy measures to empower rural women, enhance their adaptive capacities, and address the unique challenges they encounter in migrant households.